'SMASH' recommendations for standardised microscopic arthritis scoring of histological sections from inflammatory arthritis animal models. Issue 6 (18th February 2021) - Hayer, Silvia; Vervoordeldonk, Margriet J; Denis, Maria C; Armaka, Marietta; Hoffmann, Markus; Bäcklund, Johan; Nandakumar, Kutty Selva; Niederreiter, Birgit; Geka, Christina; Fischer, Anita; Woodworth, Nina; Blüml, Stephan; et al.
Abstract : Animal models for inflammatory arthritides such as rheumatoid arthritis (RA) and psoriatic arthritis are widely accepted and frequently used to identify pathological mechanisms and validate novel therapeutic strategies. Unfortunately, many publications reporting on these animal studies lack detailed description and appropriate assessment of the distinct histopathological features of arthritis: joint inflammation, cartilage damage and bone erosion. Therefore, the European consortium BeTheCure, consisting of 38 academic and industrial partners from 15 countries, set as goal to standardise the histological evaluation of joint sections from animal models of inflammatory arthritis. The consensual approach of a task force including 16 academic and industrial scientists as well as laboratory technicians has resulted in the development of the Standardised Microscopic Arthritis Scoring of Histological sections ('SMASH') recommendations for a standardised processing and microscopic scoring of the characteristic histopathological features of arthritis, exemplified by four different rodent models for arthritis: murine collagen-induced arthritis, collagen–antibody-induced arthritis, human tumour necrosis factor transgenic Tg197 mice and rat pristane-induced arthritis, applicable to any other inflammatory arthritis model. Through standardisation, the SMASH recommendations are designed to improve and maximise the information derived from in vivo arthritis experiments and to promote reproducibility and transparent reporting on such studies. In this manuscript, we will discuss and provide recommendations for analysis of histological joint sections: identification of the regions of interest, sample preparation, staining procedures and quantitative scoring methods. In conclusion, awareness of the different features of the arthritis pathology in animal models of inflammatory arthritis is of utmost importance for reliable research outcome, and the standardised histological processing and scoring methods in these SMASH recommendations will help increase uniformity and reproducibility in preclinical research on inflammatory arthritis.